PERSONALITAS NGOs DALAM PERKEMBANGAN HUKUM INTERNASIONAL MASA KINI - Aulia Nissa, Hassya (Jurnal Muhakkamah, 2020)
The actions of NGOs as an independent institution are at the forefront of enforcement and protection of human rights with activities that cross national borders, make a contribution that cannot be denied in the development of international law. Especially with the participation of NGOs as those who are actively involved in international justice institutions, and his involvement in the preparation of several important declarations in the international community. with the increasing role of NGOs in the international community, hence the position and capacity of NGOs is also questioned so the author draws a problem about the personality of NGOs in the development of international law today. This article is a normative legal research (doctrinal research), by focusing on the juridical conception of NGO personalities in International Law. The discussion begins with a description of NGOs' definitions and history, continued in the progress of NGOs so far, especially in the enforcement of human rights, following his active participation in international conventions which concluded at the conclusion, that NGOs are recognized as subjects of international law who have legal standing to be participants in both quasi-international institutions and in international convention forums with limited personality status.